Chicago Shakespeare Theater : Suiting the Action to the Word - Kozusko, Matt, 1971-; Buccola, Regina, 1969- (Book collections on Project MUSE., 2012)
"Chicago Shakespeare Theater is widely known for vibrant productions that reflect the Bard's genius for intricate storytelling, musicality of language, and depth of feeling for the human condition. Affectionately known to natives of the Windy City as "Chicago Shakes," and now in its twenty-fifth season, this vanguard of Chicago's rich theatrical tradition celebrates its silver anniversary with this bracing collection of original essays by world-renowned scholars, directors, actors, and critics. Bringing together works by such heralded figures as Terry Teachout, Jonathan Abarbanel, and Michael Billington; industry giants like Michael Bogdanov, Edward Hall, and Simon Callow; and interviews with Artistic Director Barbara Gaines and Executive Director Criss Henderson, Chicago Shakespeare Theater unveils the artistic visions and decisions that helped shape this venerable institution and examines the theater's international reputation for staging such remarkable and provocative performances"--